2020
DOI: 10.1016/j.isci.2020.101402
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic RNA 3′ Uridylation and Guanylation during Mitosis

Abstract: Summary Successful cell division involves highly regulated transcriptional and post-transcriptional control. The RNA poly(A) tail represents an important layer of RNA post-transcriptional regulation. Previous TAIL-seq analysis of S phase and M phase poly(A) tail information showed that only a small number of genes showed more than 2-fold change in their poly(A) tail length between the two cell cycle stages. In addition, the changes in poly(A) tail length between these two stages showed minimal impac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…In addition, global translation efficiency varies a lot during different stages of mitotic cell cycle, while the poly(A) tail length changed only moderately for a small proportion of genes 23 . However, we noticed extensive changes in non-A residues during somatic cell cycle 32 . Since poly(A) tail length does not contribute to translational regulation in somatic cells as seen in reproductive cells, we asked whether the non-A residues, the base composition of poly(A) tails, affect the translation efficiency.…”
Section: Non-a Residues Are Associated With High Translation Efficiency In Vivomentioning
confidence: 84%
“…In addition, global translation efficiency varies a lot during different stages of mitotic cell cycle, while the poly(A) tail length changed only moderately for a small proportion of genes 23 . However, we noticed extensive changes in non-A residues during somatic cell cycle 32 . Since poly(A) tail length does not contribute to translational regulation in somatic cells as seen in reproductive cells, we asked whether the non-A residues, the base composition of poly(A) tails, affect the translation efficiency.…”
Section: Non-a Residues Are Associated With High Translation Efficiency In Vivomentioning
confidence: 84%
“…The RNA metabolism wave is associated with the cell cycle 23 . In addition, the average/median mRNA half-life is known to be associated with cell cycle duration.…”
Section: Resultsmentioning
confidence: 99%
“…This process tends to be a key factor in germline development, differentiation, and early embryogenesis, where short-lived transcripts, with relatively fast turnover, predominate [ 33 ]. The lengths of poly(A) tails might also depend on circadian rhythms and the cell cycle [ 34 , 35 , 36 ]. By studying multiple mouse liver mRNAs, researchers demonstrated that rhythmic changes in poly(A) tail lengths were under the control of the circadian clock.…”
Section: Polyadenylation In Animal Cellsmentioning
confidence: 99%
“…With regard to the cell cycle, TAIL-Seq analysis suggests that global RNA decay takes place during the S phase through the accumulation of terminal uridylation. On the other hand, the accumulation of terminal guanylation occurs during the M phase of the cell cycle, leading to the assumption that the majority of the transcriptome is then protected from active deadenylation [ 35 ].…”
Section: Polyadenylation In Animal Cellsmentioning
confidence: 99%